Anti-plasmodial and toxicological effects of BEEMAR - a natural formulation of harnessed honeycomb bioactive compounds suspended in enhanced marine plasma - Adjei, Samuel; Obeng-Kyeremeh, Richard; Ackah, Isaac; Agbemelo-Tsomafo, Constance; Amoah, Daniel; Obeng, Stephen Asante; Asamoah, Frederick; Damanka, Susan; Danquah, Kwabena Owusu; Ntiri, Michael Preko; Honyo, Monia Enyonam; Erskine, Isaac Joe; et al. (Frontiers in Natural Products, 2025)
Introduction Increasing levels of anti-malarial drug resistance makes the development of novel drugs against malaria a necessity. Honeybee products, such as propolis, venom and honey, have been employed in traditional medicine to prevent and treat many diseases since ancient times. In theory, extracting the biologically active components of such natural products could result in the development of non-toxic and highly potent antimicrobial agents. The objectives of this study were to evaluate the pre-clinical anti-plasmodial activity and safety of BEEMAR, a patented formulation extracted from specific parts of the honeybee colony frames and suspended in-enhanced marine plasma.MethodsDifferent concentrations of the BEEMAR were tested against Plasmodium falciparum (3D7 strain) in vitro using Sybr green growth inhibitory assay and Plasmodium berghei (NK65 strain) in vivo using Rane’s test. Acute and sub-acute oral toxicity tests, based on Organization for Economic Cooperation and Development (OECD) guidelines, were used to assess the safety profile of the product.ResultsThe product demonstrated significant (p<0.05) dose-dependent inhibition of the growth of 3D7 P. falciparum strain, in vitro, with IC50 of 0.55 mg/ml. In Rane’s in vivo test, a maximum suppression of 69% was obtained at the highest dose of 1% (w/v) of the product compared to that of the standard drug, Artemether-Lumefantrine (64% at a concentration of 4mg/kg body weight) in ICR mice. Administration of the product did not result in any clinical signs of haematological or biochemical toxidromes in treated SD rats compared to the control SD rats.DiscussionThis study suggests that the BEEMAR product displays promising anti-plasmodial activity that is dose dependent. BEEMAR also exhibits an appreciable safety profile that requires further investigation.